Oral Squamous Cell Carcinoma as a Complication of Treatment for Recurrent High‐Grade Serous Cancer. (4th December 2019) - Moses, Lindsey E.; Rotsides, Janine M.; Balogun, Fiyinfolu O.; Persky, Mark S.; Muggia, Franco M.; Persky, Michael J.
Abstract : Objectives/Hypothesis: Advances in cancer treatment have increased survival for many patients, prompting a need for greater recognition of the long‐term complications of treatment. Chemotherapy agents have the potential to induce carcinogenesis and can increase the risk of secondary malignancy. Pegylated liposomal doxorubicin (PLD) used for maintenance treatment of recurrent high‐grade serous cancers has been associated with the development of oral cavity squamous cell carcinoma (SCC). Study Design: Retrospective review. Methods: Cases of oral cavity SCC in patients with recurrent high‐grade serous cancer treated with PLD between 1997 and 2017 at a single institution were reviewed. Results: Eight of 16 patients treated with PLD developed oral cavity SCC. The duration of PLD use ranged from 1.3 to 15 years (mean = 5.8 years) and cumulative dose ranged from 405 to 3, 000 mg/m 2 (mean = 1, 542 mg/m 2 ). Seven patients tested positive for BRCA mutations (four BRCA 1+, three BRCA 2+). No patients had a history of alcohol or tobacco use. All had early‐stage oral cavity disease; five were T1N0, two were T2N0, and one had carcinoma in situ. All patients underwent surgery, and two received adjuvant radiation. Four developed locoregional recurrence requiring additional treatment. Of these, one patient died from complications of oral SCC, one developed recurrent ovarian cancer, and two had no evidence of disease of the oral cavity or ovarian cancer at the last follow‐up. Conclusions: Long‐term PLD therapy may be associated with the development of oral cavity SCC. A high index of suspicion and routine head and neck examination should be included in follow‐up for exposed patients. Level of Evidence: 4 Laryngoscope, 130:2607–2610, 2020